Reading for all: a story from Chow Kit / Nurfarawahidah Badruesham - Badruesham, Nurfarawahidah (2020)
This paper presents the story of the efforts put by the Al-Bukhari Library Team that was initiated from the International Federal of Library Associations and Institutions (IFLA) 2018 paper. The project that has been done was the "Let's Read with PAB; with knowledge we lead" project and the objective of the project was to reach out to children at Jalan Chow Kit, Kuala Lumpur and helping them to have a conducive mini library as a place for them to read and learn. A mini library make over was done at Buku Jalanan Chow Kit and Sekolah Bimbingan Jalinan Kasih. These two places were selected because they provide the space for the undocumented or the homeless children to learn despite these children not attending schools. The mini libraries are equipped with books collections, toys, and computers. They serves as an informal classroom where learning activities took place every day. The children learned to read and write plus they learned to appreciate cleanliness, good health, and beauty in a carefully designed and nurturing environment. The writers evaluation is on (1) how this shelter and school operate the places after their library being make over, (2) what the benefits for the kids, volunteers and teachers, (3) what the impact to their places after "Let's Read with PAB; with knowledge we lead" project being conducted these past two years. This research employ qualitative methods with indepth interviews with volunteers, teachers, and government officers who supervise these places. This research will give benefit for librarian by developing reading modules that is more suitable for homeless kids and for volunteers in developing the library to fulfill the needs of special group like Chow Kit Kids and also give recommendations to the library team in order to sustain the reading program for homeless children by dealing with the providing and improving reading module for them.